Persahabatan Ulama Sunda - Aditia Gunawan (Manuskripta, 2018)
The book by Jajang A. Rohmana, titled Informan Sunda Masa Kolonial: Surat-surat Haji Hasan Mustapa untuk Snouck Hurgronje dalam Kurun 1894–1923 (Sundanese Informants in the Colonial Era: Letters of Haji Hasan Mustapa to Snouck Hurgronje, 1894–1923), marks a significant contribution to the historiography of Islam in West Java. This philological study examines a corpus of private letters written in Arabic sent by the renowned Sundanese poet, Haji Hasan Mustapa (1852–1930), to C. Snouck Hurgronje. Most studies on Islamic history in the Indonesian Archipelago have hitherto focused primarily on literary works, religious treatises, or the Arab-Haramayn scholarly networks, often leaving personal correspondence overlooked. In fact, private letters hold immense historical value, as they capture the author's inner psychological state, intellectual dynamics, and the broader socio-political context rich in historical data. Through a philological reconstruction of these historical fragments, Rohmana’s research not only enriches the study of Islamic history in the Sundanese lands (Tatar Sunda) but also opens a new paradigm in utilizing epistolary sources for writing the history of the Archipelago. === Buku karya Jajang A. Rohmana yang berjudul Informan Sunda Masa Kolonial: Surat-surat Haji Hasan Mustapa untuk Snouck Hurgronje dalam Kurun 1894–1923 menjadi kontribusi penting dalam historiografi Islam di Jawa Barat. Penelitian filologis ini mengkaji korpus surat-surat pribadi berbahasa Arab yang dikirimkan oleh pujangga Sunda, Haji Hasan Mustapa (1852–1930), kepada C. Snouck Hurgronje. Kebanyakan kajian sejarah Islam Nusantara selama ini berfokus pada karya literer, kitab keagamaan, atau jaringan keilmuan Arab-Haramayn, sehingga dokumen korespondensi pribadi kerap terabaikan. Padahal, surat-surat pribadi memiliki nilai historis yang sangat tinggi karena mampu merekam situasi batin, dinamika pemikiran, serta konteks sosial-politik zaman yang kaya akan data sejarah. Melalui rekonstruksi filologis terhadap serpihan sejarah ini, penelitian Rohmana tidak hanya memperkaya studi sejarah Islam di Tatar Sunda, tetapi juga membuka paradigma baru dalam pemanfaatan sumber-sumber epistolari untuk penulisan sejarah Nusantara.